Implementasi Media Quizizz dalam Meningkatkan Hasil Belajar Mata Pelajaran Pendidikan Pancasila Materi Penerapan Pancasila dalam Kehidupan Sehari-Hari pada Peserta Didik Kelas VB SD Negeri 47 Palembang - Fikry Kurniawan; Hudaidah Hudaidah; Helen Saputri (Mathematics Education Study Program, 2025)
This study aims to determine the effect of using Quizizz media in improving learning outcomes in Pancasila education subjects for class VB students at SD Negeri 47 Palembang, especially in the material on the application of Pancasila in everyday life. The research method used is classroom action research (CAR) consisting of two cycles. The subjects of the study were 30 class VB students, who were tested with a pretest before the implementation of Quizizz media and a posttest after cycle 1 and cycle 2. The pretest results showed that the average student score was 60 with 40% completion. After the implementation of Quizizz media in cycle 1, the average posttest score increased to 75 with 70% completion. In cycle 2, the average posttest score increased again to 85 with 90% completion. These findings indicate that the use of Quizizz media significantly improves students' understanding of Pancasila values ​​and their application in everyday life. Therefore, it is suggested that this interactive media be applied in learning other subjects to improve students' motivation and learning outcomes. Thus, the study can conclude that this Quizizz educational game-based learning media not only makes it easier for teachers to deliver learning materials, but can also improve students' learning outcomes and their understanding in classroom learning for students.